Integrated Network Pharmacology and Lipidomics to Reveal the Inhibitory Effect of Qingfei Oral Liquid on Excessive Autophagy in RSV-Induced Lung Inflammation - Lin, Lili; An, Li; Chen, Hui; Feng, Lu; Lu, Mengjiang; Liu, Yuling; Chu, Chu; Shan, Jinjun; Xie, Tong; Wang, Xiaorong; Wang, Shouchuan (Frontiers in Pharmacology, 2021)
Background: Respiratory syncytial virus (RSV) can cause varying degrees of lung inflammation in children. Qingfei Oral Liquid (QF) is effective in treating childhood RSV‐induced lung inflammation (RSV-LI) in clinics, but its pharmacological profiles and mechanisms remain unclear. Methods: This study combined network Pharmacology, lipidomics, pharmacodynamics, and pathway validation to evaluate the therapeutic mechanisms of QF. Using Cytoscape (v3.8.2) and enrichment analyses from the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO), a global view of the putative compound-target-pathway network was created. The corresponding lipidomic profiles were then used to detect differently activated lipids, revealing the metabolic pathway, using ultra-high-performance liquid chromatography linked to hybrid Quadrupole-Exactive Orbitrap mass spectrometry (UHPLC-Q-Exactive Orbitrap MS). Meanwhile, the in vivo efficiency of QF, the enrichment pathway, and the excessive autophagy inhibition mechanisms were validated in RSV‐infected mice models. Results: The network pharmacology results demonstrated 117 active compounds acted directly upon 101 core targets of QF against RSV‐LI. The most significantly enriched pathway was the PI3K/Akt/mTOR signaling pathway (p < 0.05). In addition, untargeted lipidomics were performed, and it was revealed that higher lung levels of DAG 30:0, DAG 30:5, DAG 32:0, DAG 16:0_18:0, DAG 17:0_17:0, DAG 34:1, DAG 36:0, DAG 36:1 in the model group were decreased after QF administration (FDR < 0.05, FC > 1.2). According to immunohistochemistry assay, lipin-1, a key enzyme in DAG synthesis, was upregulated in the RSV-LI mouse model but downregulated following QF administration. Animal experiments further validated that QF suppressed the PI3K/Akt/mTOR/ signaling pathway-related proteins with lower lung levels of phosphorylated forms of PI3K, AKT, and mTOR in the QF group (P < 0.01). Finally, pharmacodynamic investigations indicated that QF reduced airway inflammation caused by excessive autophagy by decreasing lung levels of RSV F and G proteins, VPS34, Beclin-1, Atg5, and LC3B II, IL-1 and TNF-α (P < 0.05). Conclusion: Lipidomic-based network pharmacology, along with experimental validation, may be effective approaches for illustrating the therapeutic mechanism of QF in the treatment of RSV‐LI.